Student perceptions of innovation indicators in general education: insights for enhancing knowledge and practice - El Sleemi, Mash’al; Al Jughaiman, Abdullah; Al Fawzan, Sarah (Frontiers in Education, 2025)
This study explores the current practice of innovation-promoting indicators in general education schools in Saudi Arabia, specifically from the perspective of students. Using a descriptive approach, the study surveyed 1,717 high school students in the Eastern Region, including 1,595 regular students and 122 gifted students, who were selected through random sampling. A questionnaire was designed to assess the extent to which these innovation indicators are implemented. The findings revealed a moderate overall implementation of these indicators, with an average score of 2.77. The curriculum indicator ranked highest (3.14), while the educational environment indicator ranked lowest (2.56). Notably, there were significant differences between regular and gifted students regarding the overall innovation indicators, particularly in the areas of curriculum, the role of the student, and the educational environment, all favoring gifted students. However, no significant differences were observed between the two groups concerning the role of school administration and teachers in fostering innovation. This study underscores the importance of revising and enhancing curricula to better stimulate innovative thinking among students, thus strengthening their capacity for innovation. Its findings provide valuable insights for improving educational practices and policies, particularly in fostering environments that support creative and critical thinking.